Software vulnerability discovery and disclosure system: a systems dynamics approach - Lewis, Paul (Cranfield University, 2016)
3MT (three minute thesis) presented at the 2016 Defence and Security Doctoral Symposium. This research investigates this critical issue of software vulnerabilities within commercial-off-the-shelf (COTS) software. More specifically, what are the dynamics and structures of the system that is driving the increased rate of discovery, and furthermore, what impact do new innovations, policy or otherwise, have in both upon the system and in decreasing the risk organisations face. The ultimate aim of this research is to evolve the underlying theory and models, ground it in real empirical data and provide a framework to increase the understanding of the vulnerability discovery and disclosure system.
Keywords: 'Software'; 'Vulnerability'; 'Systems dynamics'; 'DSDS16 3MT'; 'DSDS16'; 'Computer System Security'